O parto dos caminhos: Formação dos Sindicatos Rurais no Rio Grande do Norte (1960 - 1964) - Rocha Filho, Ruy Alkmim (2005)
The present work treats the movements dedicated to reinvidication per land and social rights for the field works, among 1960 and 1964. Trying to understand this question in the Rio Grande do Norte it is necessary to consider the connection between the catholic church and the rural syndicates besides the influence of the Brazilian communist party, and still other social movements and the state. The structures politics local, national and international, had considerable importance to the organization rural potiguares workers. The rural potiguares syndicate appear in 1961 - after a hard organization work starting of the Service of Rural Assistance - and expand itself through state until the middle of 1962. Soon the first big conflicts an important manifestation are perceive, indirectly referring to a increasing movement's performance. The Favoring Progresses chains co quested a biggest influence in the politics destiny of the Rio Grande do Norte, in front of integration among syndicates, educational projects, and favoring progress's politics. But the military coup hired that the hope overflow the field